Association of Malnutrition, Left Ventricular Ejection Fraction Category, and Mortality in Patients Undergoing Coronary Angiography: A Cohort With 45,826 Patients - Mai, Ziling; Huang, Zhidong; Lai, Wenguang; Li, Huanqiang; Wang, Bo; Huang, Sumei; Shi, Yingming; Yu, Sijia; Hu, Qizheng; Liu, Jin; Zhang, Lingyu; Liu, Yong; et al. (Frontiers in Nutrition, 2021)
Background: The regulatory effect of the left ventricular ejection fraction (LVEF) categories on the relation between malnutrition and all-cause mortality in patients underwent coronary angiography (CAG) have not been adequately addressed. Methods: 45826 patients consecutively enrolled in the Cardiorenal ImprovemeNt (CIN) study (ClinicalTrials.gov NCT04407936) from January 2008 to July 2018 who underwent coronary angiography (CAG). The Controlling Nutritional Status (CONUT) score was applied to 45826 CAG patients. Cox regression models were used to estimate hazard ratios for mortality across combined LVEF and/or malnutrition categories. Population attributable risk (PAR) was estimated for eight groups stratified by nutritional status and LVEF categories. Results: In our study, 42181(92%) of patients were LVEF ≥40%, of whom, 41.55% and 9.34% were in mild and moderate or severe malnutrition status respectively among patients with LVEF ≥40%, while 46.53% and 22.28% in mild and moderate or severe malnutritional status among patients with LVEF<40%. During a median follow-up time of 4.5 years, 5350(11.7%) patients died. After fully adjustment, there is no difference of mortality on malnutrition in LVEF<40% group (mild, moderate and severe vs. normal, HR (95%CI): [1.00(0.83-0.98)], [1.20(0.95-1.51)], [1.41(0.87-2.29)], respectively, p for trend =0.068), but malnutrition was associated with significantly increased risk of mortality in LVEF ≥40% group (mild, moderate and severe vs. normal, HR (95%CI): [1.21(1.12-1.31)], [1.56(1.40-1.74)] and [2.20(1.67-2.90)] respectively, p for trend <0.001, and p for interaction <0.001). Patients with LVEF≥40% had higher malnutrition-associated risk of mortality and PAR than those with LVEF<40%. Conclusions: Malnutrition is common in CAG patients and it has a greater effect on all-cause mortality and a higher PAR in patients with LVEF≥40% than LVEF<40%.